A hybrid of surrogate model and MIGA method for optimization and compensation of steady-state flow force on water hydraulic HSV. (August 2022) - Nie, Songlin; Hong, Ruidong; Ji, Hui; Liu, Qingtong; Nie, Shuang
Abstract: In this research, a hybrid of surrogate model and Multi-island genetic algorithm (MIGA) is proposed for optimization and compensation of steady-state flow force on water hydraulic high-speed on-off valve (HSV) driven by voice coil motor. Firstly, a dynamic model on the spool of HSV is established, and the effects of spool displacement, spool half-cone angle, valve stem diameter and inlet pressure on the steady-state flow force of HSV are analyzed through the CFD simulation. Secondly, a quadratic response surface model is set up based on design of experiment (DOE) to analyze interactions of key parameters on steady-state flow force. MIGA is proposed to optimise the structural parameters of HSV, and the optimization results are analyzed and verified by CFD simulations. Simulation results demonstrate that the steady-state flow force is reduced significantly. Finally, the steady-state flow force in the optimized structure of HSV is also verified experimentally. The experiment results exhibit that the optimized spool can compensate about 71% for the steady-state flow force, then reduce about 15% the energy consumption of HSV. This research will provide the guide for the design and engineering application of HSV. Highlights: Using the momentum theorem to analysis steady-state flow forces on the spool. Using CFD techniques to analyze the influence of spool structural parameters on steady-state flow force. Using surrogate model and MIGA to obtain optimal solution of HSV. Optimized structure to effectively compensate for steady-state flow forces and reduce VCM energy consumption.